EVALUASI PELAYANAN PROGRAM JAMPERSAL : TINJAUAN DIMENSI MUTU PELAYANAN JAMPERSAL - Mulyati, Leli (Politeknik Kesehatan Kemenkes Bengkulu, 2013)
Knowing the factor fo pregnant women to choose jampersal service health center in the region of Curup Year 1012. The research is using descriptive design. The sampling using purposive sampling. With 67 people and count using univariant. From this study it can be seen from the technical competence almost half of respondents (48.2%) responded strongly agree, Access to almost all respondents (52.23%) responded agree. The effectiveness of almost all respondents (51.23%) responded agree. Continuity of care almost all respondents (51.73%) responded agree, security is almost all respondents (51.23%) responded agree. Human interpersonal almost all respondents (52.76%) responded agree, and the comfort of pleasure almost all respondents (50.23%) responded agree. Based the conclusion, of the 67 respondents can be concluded the vast majority of respondents (52.23%) said quality of care at health centers is good and almost Curup majority of respondents (47.76%) stated quality of care at health centers Curup not good.